Notes on Growth and Flowering Behaviour of Liparis cordifolia J.D. Hook (Orchidaceae) a Beautiful Terrestrial Orchid - Pal, Ram; Nagrare, V. S.; Dayamma, M. (Indian Forester, 2010)
Liparis cordifolia is a cool growing terrestrial orchid distributed in Himalayan region. Small sized-plant, and its heart-shaped shining solitary leaf, long lasting elongating raceme and low light requirement during cultivation make it an attractive plant for indoor decoration. The growth and flowering behavior of this species under Darjeeling conditions are reported. The shoot bud arised in July and August from basal part of the pseudobulb and inflorescence emerged from the top of recently formed stem (pseudobulb) 23.8 days after initiation of shoot bud. The first flower bud opened in the last week of September to October, 15.12 days after emergence of flower buds. The raceme remained in flower for 54.18 days up to first week of December. The growth phase marked by emergence of roots from the basal part of stem and swelling of pseudobulb in last week of November to first week of December. This phase lasted for 183.81 days. The plants proceeded to dormancy after senescence and drying of leaf in April and May. The data on morphological characters like pseudobulb length and width, leaf length and width, inflorescence length, raceme length, number of flowers are tabulated. Inflorescence length, raceme length and number of flowers were found to determine by length and width of previous years growth (pseudobulb). The various plant parts when compared with colour chart developed by Royal Horticulture Society showed different shades of green yellow colour. The leaves were found to have deepest (RHS 146 A, 146 B, and 147 A) and sepals and petals lightest green yellow color (RHS 145 C and 145 D).